2016
DOI: 10.9734/ajea/2016/26144
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Pansy (Viola wittrockiana Gams.) to the Quality of the Growing Media

Abstract: The quality of the growing medium stands out as one of the most important factors affecting the success of annual plants, especially when grown in potted culture. Recently, we have suggested that growing medium gives not only a matrix for water and nutrient absorption but also a source of external signalling. The aim of this work was to assess the performance of six pansy (Viola wittrockiana Gams.) genotypes grown in two growing media with significant differences in both physical and chemical properties, aimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Bailey-Serres and Colmer [11] and Voesenek and Sasidharan [12] have indicated that a lack of oxygen inhibits respiration, decrease metabolic plant adaptations to cope with the hypoxic and anoxic conditions and resulting energy deficits, as well as change anatomical and morphological adaptations to improve internal O 2 supply. These metabolic changes would give the same effects on endogenous cytokinin synthesis as plug cell volume [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Bailey-Serres and Colmer [11] and Voesenek and Sasidharan [12] have indicated that a lack of oxygen inhibits respiration, decrease metabolic plant adaptations to cope with the hypoxic and anoxic conditions and resulting energy deficits, as well as change anatomical and morphological adaptations to improve internal O 2 supply. These metabolic changes would give the same effects on endogenous cytokinin synthesis as plug cell volume [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…An ornamental crop undergoes different abiotic stresses during commercial production cycle, which decrease both plant growth and quality. Previous reports from our laboratory have shown that plug cell volume [1,2] and growing media quality [3][4][5][6][7] would be considered as abiotic stresses. Negative growth effects on nursery remain and increase during the pot growth phase [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Soilless substrates are used in horticulture for growing seedlings, plant propagation, and ornamental plant production due to its high physical and chemical stability and low degradation rate, but peat mixes are not necessarily the optimal growth substrates because of their water-logging tendency and low oxygen availability under watering. Alternative soilless growing media can be better than peat for several ornamental bedding plants [6,7,14,15), including Impatiens walleriana [4,9,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viola wittrockiana Gams. is a commercially important cool season garden crop for landscape, and one of the five best-selling bedding plants in both developed and undeveloped countries (Gandolfo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%